2014
DOI: 10.1007/s10787-014-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gastric mucosal inflammatory responses to Helicobacter pylori via ghrelin-induced protein kinase Cδ tyrosine phosphorylation

Abstract: A peptide hormone, ghrelin, plays a key role in modulation of gastric mucosal inflammatory responses to Helicobacter pylori by controlling the activation of constitutive nitric oxide synthase via Src/Akt-dependent phosphorylation that requires phosphatidylinositol 3-kinase (PI3K) participation. Here, we examined the relationship among PI3K; its upstream effector, protein kinase C (PKC); and cSrc. We show that stimulation of gastric mucosal cells with H. pylori LPS leads to the activation and membrane transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The PI3K inhibitor LY294002 suppressed phosphorylation events, indicating that ghrelin activates the PI3K/AKT/mTOR pathway through phosphorylation. Two other studies, one examined the modulatory effect of ghrelin on gastric mucosal prostaglandin and nitric oxide and another examined gastric mucosal inflammatory responses to Helicobacter pylori , also showed that ghrelin activates the PI3K/AKT/mTOR pathway in different ways[46,47] (Figure 2). Whether ghrelin promotes the development and progression of GISTs through this or other mechanisms remains unclear.…”
Section: Ghrelin Activates Pi3k/atk/mtor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K inhibitor LY294002 suppressed phosphorylation events, indicating that ghrelin activates the PI3K/AKT/mTOR pathway through phosphorylation. Two other studies, one examined the modulatory effect of ghrelin on gastric mucosal prostaglandin and nitric oxide and another examined gastric mucosal inflammatory responses to Helicobacter pylori , also showed that ghrelin activates the PI3K/AKT/mTOR pathway in different ways[46,47] (Figure 2). Whether ghrelin promotes the development and progression of GISTs through this or other mechanisms remains unclear.…”
Section: Ghrelin Activates Pi3k/atk/mtor Pathwaymentioning
confidence: 99%
“…Specific mechanism of ghrelin involved in the protection of pulmonary artery endothelial cells and activation of the PI3K/AKT/mTOR pathway in human pulmonary artery endothelial cells[44-47]. Solid lines represent activating actions, and dotted lines represent inhibitory actions.…”
Section: Ghrelin Activates Pi3k/atk/mtor Pathwaymentioning
confidence: 99%
“…Recently, we have reported on the role of PKCδ in modulation of gastric mucosal inflammatory responses to H. pylori LPS by ghrelin. Our results revealed that while the LPS-elicited PKCδ activation leads to PI3K phosphorylation on Ser that exerts the detrimental influence on the kinase activity, the effect of ghrelin is manifested by phosphorylation of PKCδ and PI3K on Tyr, and associated with up-regulation in the kinase activation [31]. In the present study, we investigated the involvement of PKCδ in controlling the posttranslational processes of cNOS activation through phosphorylation associated gastric mucosal inflammatory responses to H. pylori LPS and ghrelin.…”
Section: Introductionmentioning
confidence: 85%
“…The downregulated level of ghrelin in the gastric mucosa of H. pylori -infected patients might promote an ongoing Th1-cell response and chronic active gastritis [48]. B. L. Slomiany and A. Slomiany [49] reported the role of phosphatidylinositol 3-kinase (PI3K) in digestive tract mucosa infected with H. pylori , demonstrating that the modulation of ghrelin as a gastric mucosal response to H. pylori depends on PI3K activation. The ghrelin receptor is highly specific, which means that only the acylated form of ghrelin can bind to it, and active ghrelin stimulates the appetite though neuropeptide Y (NPY).…”
Section: Caga-positive H Pylori Strains-related Diseases (Figure 1)mentioning
confidence: 99%